Circulating Levels of Low-Density Granulocytes and Cell-Free DNA as Predictors of Cardiovascular Disease and Bone Deterioration in SLE Patients - Suárez, Ana; Tobío-Parada, Uxía; Rodríguez-Carrio, Javier; Martínez-Zapico, Aleida; Pérez-Álvarez, Ángel I.; Suárez-Díaz, Silvia; Caminal-Montero, Luis; López, Patricia (Thrombosis and Haemostasis, 2024)
The present work evaluates the predictive value of low-density granulocytes (LDGs) for the development of cardiovascular disease (CVD) and/or bone deterioration (BD) in a 6-year prospective study in systemic lupus erythematosus (SLE). Considering the high SLE-LDG capacity to form neutrophil extracellular traps (NETs), circulating levels of total cell-free DNA (cirDNA) and relative amounts of mitochondrial and nuclear DNA (mtDNA and nDNA, respectively) were tested as LDG-associated biomarkers to identify SLE patients at risk of CVD and BD.The frequency of total blood LDGs, as well as the CD16negCD14neg (nLDG) and CD16posCD14low (pLDG) subsets, was quantified by flow cytometry in 33 controls and 144 SLE patients. Total cirDNA and relative amounts of mitochondrial (mtDNA) and nuclear (nDNA) cell-free DNA were measured by fluorometry or qPCR in plasma from a subgroup of 117 patients and 23 controls at enrolment.Our findings showed increased blood levels of SLE-nLDGs at enrolment associated with prospective CVD development (pCVD) and the presence of BD, thus revealing LDG expansion as a predictor of both comorbidities in SLE progression. The amounts of the different types of circulating DNA analyzed were increased in patients, especially those presenting with traditional CV risk factors or subclinical atheromatosis. Similar to nLDGs, the nDNA concentration could predict the development of pCVD in SLE, supporting the quantification of cirDNA levels as a surrogate marker of LDGs in clinical practice.
Keywords: low-density granulocytes (LDGs); circulating cell-free DNA (cirDNA); cardiovascular disease (CVD); bone loss; systemic lupus erythematosus (SLE)